Dietary Phospholipid-Bound Conjugated Linoleic Acid and Docosahexaenoic Acid Incorporation Into Fetal Liver and Brain Modulates Fatty Acid and N-Acylethanolamine Profiles - Murru, Elisabetta; Carta, Gianfranca; Manca, Claudia; Saebo, Asgeir; Santoni, Michele; Mostallino, Rafaela; Pistis, Marco; Banni, Sebastiano (Frontiers in Nutrition, 2022)
We evaluated whether maternal intake of conjugated linoleic acid (CLA) and docosahexaenoic acid (DHA) in the phospholipid (PL) form (CLA-DHA PL) affects maternal and fetal brain and liver fatty acids (FAs) profile and the biosynthesis of FA-derived bioactive lipid mediators N-acylethanolamines (NAEs) involved in several neurophysiological functions. We fed rat dams during the first 2/3 of their pregnancy a CLA-DHA PL diet containing PL-bound 0.5% CLA and 0.2% DHA. FA and NAE profiles were analyzed in maternal and fetal liver and brain by Liquid Chromatography diode array detector (LC-DAD) and MS/MS in line. We found that CLA and DHA crossed the placenta and were readily incorporated into the fetal liver and brain. CLA metabolites were also found abundantly in fetal tissues. Changes in the FA profile induced by the CLA-DHA PL diet influenced the biosynthesis of NAE derived from arachidonic acid (ARA; N-arachidonoylethanolamine, AEA) and from DHA (N-docosahexaenoylethanolamine, DHEA). The latter has been previously shown to promote synaptogenesis and neuritogenesis. The reduced tissue n6/n3 ratio was associated to a significant decrease of AEA levels in the fetal and maternal liver and an increase of DHEA in the fetal and maternal liver and in the fetal brain. Maternal dietary CLA-DHA PL by promptly modifying fetal brain FA metabolism, and thereby, increasing DHEA, might represent an effective nutritional strategy to promote neurite growth and synaptogenesis and protect the offspring from neurological and psychiatric disorders with neuroinflammatory and neurodegenerative basis during the critical prenatal period.